Efficiency of Combined Cryopreservatives Containing Glycerol or 1,2-Propanediol During Freezing of Erythrocytes - Ramazanov, V. V. (Problems of Cryobiology and Cryomedicine, 2011)
The osmotic properties of erythrocytes frozen-thawed in combined cryopreservatives, containing polymeric non-penetrating (dextran, polyethylene glycol) and penetrating (glycerol, 1,2-propane diol) cryoprotectants were studied. It was established that in erythrocytes frozen-thawed in the presence of polymers the increasing of H+ ion flow rate and osmotic fragility in the environment with 0.45–0.9% NaCl was observed. It is sufficient to add 5% glycerol or 1,2-propane diol (1,2-PD) to the medium to preserve osmotic properties of frozen-thawed cells. The obtained results enable to suggest that cryoprotective efficiency of combined cryopreservatives, containing non-penetrating and penetrating cryoprotectants is determined both by the contribution of cryoprotective components differing by action mechanism into the sum protection efficiency during freezing-thawing and by the weakening of posthypertonic stress in cells during freeze-thawing.